COMPARING LIVING AND HOLOCENE COCCOLITHOPHORE ASSEMBLAGES IN THE AEGEAN MARINE ENVIRONMENTS - Dimiza, M. D.; Triantaphyllou, M. V. (Bulletin of the Geological Society of Greece, 2010)
Detailed quantitative analyses of coccolithophores performed on the shallow deposits of the southeastern Aegean region (core NS-14, 505 m depth), evidenced that the distribution of calcare-ous nannoplankton assemblages during the last 13 ka BP reflects paleoenvironmental changes which are directly related to parameters such as temperature, salinity, productivity and nutrient flux in the water column. Analysis enabled the separation of the assemblages in four groups. Group A consists of Emiliania huxleyi and the subtropical species Syracosphaera spp. and Rhabdosphaera clavigera, Group B is composed of Helicospaera spp. and Florisphaera profunda, typical species for high productivity conditions in the middle-lower photic zone, Group C consists of Gephyrocapsa oceanica and Braarudosphaera bigelowii, that characterise low salinity conditions and Group D includes Umbilicosphaera spp. and Calcidiscus spp. which are described as relatively eutrophic species. The Holocene assemblages differ distinctly from the living coccolithophore communities in the coastal ecosystems of the Aegean Sea, where only Group A coccolithophores are thriving in the seasonally controlled marine environment.